1) 2√3(√12+3√5)-√5(6√3-√20) 2) √6(0,5√24-8√11)-4√11(√99-2√6)

0 голосов
121 просмотров

1) 2√3(√12+3√5)-√5(6√3-√20)

2) √6(0,5√24-8√11)-4√11(√99-2√6)


Скачать вложение Word (DOC)
Скачать вложение Word (DOC)

Алгебра (12 баллов) | 121 просмотров
Дано ответов: 2
0 голосов

2√3(√12+3√5)-√5(6√3-√20)=2√3 (4*3+3√5)- √5(6√3-√4*√5)=2√3(2√3+3√5)-√5(6√3-2√5)=12+2√15-6√15+10=22

 

 √6(0,5√24-8√11)-4√11(√99-2√6)=  √6(0,5√4*√6-8√11)-4√11(√11√9-2√6)=

√6(√6-8√11)-4√11(3√11-2√6)=6-8√66-132+8√66=-126

(18 баллов)
0 голосов

решение находится во вложении


Скачать вложение Word (DOC)
(499 баллов)